2015
DOI: 10.1210/jc.2015-2478
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Phthalate in the Pathogenesis of Endometriosis: In Vitro, Animal, and Human Data

Abstract: These findings strongly suggest that exposure to phthalate may lead to establishment of endometriosis by enhancing invasive and proliferative activities of endometrial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 36 publications
5
65
0
Order By: Relevance
“…These results could be particularly relevant, as for male fetuses, to detect early sexual dysmorphism. In addition, in accordance to M a n u s c r i p t 12 previous studies [29,30] demonstrating the risk of developing endometriosis linked to exposure to phthalates and to xeno-estrogenes, abnormalities in the AGD in female foetuses might be a parameter to take into account in further studies to better understand the physiopathology of this debilating disorder.…”
Section: Discussionsupporting
confidence: 58%
“…These results could be particularly relevant, as for male fetuses, to detect early sexual dysmorphism. In addition, in accordance to M a n u s c r i p t 12 previous studies [29,30] demonstrating the risk of developing endometriosis linked to exposure to phthalates and to xeno-estrogenes, abnormalities in the AGD in female foetuses might be a parameter to take into account in further studies to better understand the physiopathology of this debilating disorder.…”
Section: Discussionsupporting
confidence: 58%
“…However, the adverse effects of phthalates on the human reproductive system are largely unknown. Many studies suggest that phthalates contribute to the pathogenesis of endometriosis [16,17,18]. Similar to endometriosis, leiomyoma are estrogen sensitive; therefore, endocrine-disrupting chemicals may play a role in their development.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the weak estrogenic and antiandrogenic effect of phthalates, several studies have shown the possible association of exposure to phthalate with common estrogendependent diseases, such as premature thelarche (14,15), pubertal gynecomastia (16), endometriosis (17)(18)(19)(20), and breast cancer (21). With respect to uterine leiomyoma, one study revealed that women with leiomyoma have significantly higher levels of total urinary MEHP levels compared with controls (22).…”
mentioning
confidence: 99%